Introduction to Computer Graphics - Eck, David J.; Open Textbook Library (Open Textbook Library, 2016)
Introduction to Computer Graphics is a free, on-line textbook covering the fundamentals of computer graphics and computer graphics programming. This book is meant for use as a textbook in a one-semester course that would typically be taken by undergraduate computer science majors in their third or fourth year of college.
Chapter 1: Introduction -- Chapter 2: Two-Dimensional Graphics -- Chapter 3: OpenGL 1.1: Geometry -- Chapter 4: OpenGL 1.1: Light and Material -- Chapter 5: Three.js: A 3D Scene Graph API -- Chapter 6: Introduction to WebGL -- Chapter 7: 3D Graphics with WebGL -- Chapter 8: Beyond Realtime Graphics -- Appendix A: Programming Languages -- Appendix B: Blender: A 3D Modeling Program -- Appendix C: Gimp and Inkscape for 2D Graphics -- Appendix D: Source Code for Sample Programs -- Appendix E: Glossary
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks